Transformative Teaching of Criminal Law with Human Sense for Access to Justice. The Experience of the Model at the Tecnologico de Monterrey - García Sánchez, Arán (2024)
The educational and labor panorama of the Law Career in Mexico is a challenge; 3440 institutions offer it, 13 % of which are accredited, raising doubts about its quality. The traditional teaching of Criminal Law perpetuated dogmatism, without criticism in the students. In contrast, Tecnológico de Monterrey innovated with learning through ethical and citizen competencies and clinical teaching, which theorizes in reality. The «Voice of the Victims» program integrated professionalism with access to justice for groups in vulnerable situations. Through the Criminal Law and crimes block, especially in the «Tec21»educational model, the study of feminicide corroborates the hypothesis that framing the behavior within the typical description is not enough for its comprehensive vision. Likewise, it limits the purposeful exercise of its reduction.